Ternary Electronic Logic Systems Automation: A Novel Study Based on VHDL Language Third Part: Ternary Non-Combinational (Sequential) Logic Components - Al-Humidi, Abdullah Ali; Asaad, Abdulraqib Abdo (University of Science and Technology, Yemen, 2020)
In this scientific paper, the third part of the software library for the Ternary non-combinational (Sequential) logic components (the components that store information) will be built based on VHDL language starting by the Ternary D Latch (TDL) and ending by the Ternary RAM (TRAM).